Sandwich Theorems for Some Analytic Functions Defined by Convolution (European Journal of Pure and Applied Mathematics, 2009)
For certain analytic functions defined by convolution products, we obtain several applications of first order differential subordination and superordination, that generalize some previous results obtained by different authors.